AB1273 Uptake of pneumococcal and influenza vaccination in patients receiving biological dmards (BDMARDS) in ireland. (12th June 2018) - Ng, W.L.; Anjum, A.; Sebastian, A.; Brady, M.; Fitzgerald, E.; McCarthy, B.; Gillespie, M.; Doran, J.P.; Devlin, J.; Fraser, A.
Abstract : Background: Biological disease-modifying antirheumatic drugs (bDMARDs) have made significant positive outcomes in the lives of patients with rheumatic disease. This treatment has proven efficacy in delaying joint destruction and inducing disease remission. 1 Studies have shown that pneumococcal vaccination is cost effective while the influenza vaccination significantly prevents morbidity and mortality in the elderly and in patients with chronic disease. 1 Objectives: To evaluate the pneumococcal and influenza vaccination status in patients receiving biological disease-modifying antirheumatic drugs (bDMARDs). Methods: Patients on bDMARDs attending the rheumatology infusion unit were asked about their vaccination status on pneumococcal and influenza using a questionnaire. The patients' diagnosis, current bDMARD and reasons for not having had vaccination were recorded. Results: 92 patients were recruited. Mean age of 53.2 years with 63 (68.5%) female and 29 (31.5%) male. A total of 30 (32.6%) patients received both pneumococcal and influenza vaccination, 1 (1.1%) received pneumococcal vaccination alone, 22 (23.9%) received influenza vaccination alone and 39 (42.4%) had neither. Of the 18 (19.6%) patients age >65 years, 5 (27.8%) received influenza vaccination alone and 8 (44.4%) received both. Patients who did not receive vaccinations were given an educational booklet. The most common diagnosis from our cohort was rheumatoid arthritis(37%), followed by spondyloarthritis(13%), Behçet's disease(9.8%), myositis(7.6%), vasculitis(5.4%), systemic lupus erythematosus(5.4%), psoriatic arthritis(4.4%) and others(17.4%). 48 (52.2%) were on rituximab, 37 (40.2%) on infliximab, 6 (6.5%) were on tocilizumab and 1 (1.1%) was on abatacept. Of the 61 (66.3%) patients who did not receive the pneumococcal vaccine, 44 (72.1%) were unaware of its availability, 6 (9.8%) were not interested in receiving it, 4 (6.6%) were afraid of the side effects, 4 (6.6%) declined vaccination and 3 (4.9%) were unaware it was recommended. 40 (43.5%) who did not receive the influenza vaccine stated that they were either unaware(45%), not interested(25%), declined vaccination(10%), forgotten(5%), unaware it was recommended(5%) and afraid of the side effects(2.5%). 3 (7.5%) had previous bad experiences from influenza vaccination. Conclusions: This is the first study in Ireland looking at vaccination uptake in patients on bDMARDS. The vaccination rate in our cohort was less than satisfactory. Patients on immunosuppressants are recommended to have these vaccinations and preferably to receive them before commencing on the immunosuppressants. 2 The lack of awareness is the main reason for failure to be vaccinated. Hence, primary care physicians and the rheumatology team should take active roles in increasing awareness amongst patients about the recommendation for pneumococcal and influenza vaccination. References: [1] Doe S, Pathare S, Kelly CA, et al. Uptake of influenza vaccination in patients on immunosuppressant agents for rheumatological diseases: a follow-up audit of the influence of secondary care. Rheumatology. 2007;46:715–6 [] 2Assen S V, Agmon-Levin N, Elkayam O, et al. EULAR recommendations for vaccination in adult patients with autoimmune inflammatory rheumatic diseases. Ann Rheum Dis. 2011;70:414–22 Disclosure of Interest: None declared